An Analysis of Imperative Sentence in â€œUang Panaiâ€ Movie - Muhammand Fajri Hidayatullah; Dedi Rahman Nur (Center of Language and Cultural Studies [CLCS], 2019)
This study aimed to analyze the type and function of the Imperative sentence that appeared in â€œUang Panaiâ€ Movie. The researcher applied content analysis design. The subject of this study is the characters in â€œUang Panaiâ€ Movie. And the object of study was imperative sentences used by the characters in the movie. The instrument used in this study was the checklist. The researcher found 98 positive imperative sentences and 30 Negative imperative sentences. The particles used in a positive imperative sentence in Bugise Language found in Uang Panai Movie mostly the character used particle to stress the command and also the researcher found that in Bugise imperative there are using Ko and Ki to represent you but Ki is more polite than using ko. The researcher also found 83 imperative sentences as command with the most particle used is to give emphasis to the listener to do something, 14 imperative sentence as a request with the most marker used is marker ki to represent politeness and word â€œtolongâ€ and 30 imperative sentence as a prohibition used word â€œjanganâ€ with mostly marker used is ko to give more stress to the listener for not to do something.